Analysis of Disaster Vulnerability Areas in West Bandung Regency, West Java, Indonesia - Usman, Dudi Nasrudin; Sukarsih, Icih; Permanasari, Yurika; Mildani, Deni; Widayati, Sri; Nuryahya, Himawan; Pulungan, Linda; Ramadhani, Rully Nurhasan (Journal of Geoscience, Engineering, Environment, and Technology, 2023)
Mineral resources, coal, and rock are one of the potentials possessed by Indonesia to be able to earn income from the mining sector. West Bandung Regency is one of the areas that have quite a lot of potential rock and mineral resources. The potential of this area is quite large, namely andesite rock, sand, limestone, and sandstone. Zeolite and others. On the other hand, the West Bandung area has a high potential and threat of being a disaster-prone. West Bandung Regency has the highest number of natural disasters occurring in the type of landslide disaster, which occurred 52 times in the period 2008-2016, or 68% of all disasters. Loss of economic value also occurs for mining material resources which are limited by the existence of a disaster zone. So it is necessary to carry out mitigation from the start to map disaster areas that have an impact on the distribution and existence of mining material resources. This study aims to identify and analyze the potential of rock resources in disaster-prone areas, so as to be able to prioritize conservation aspects for potential mining materials. The method used in this research is through literature study, mapping the potential of mining materials, mapping the potential of disaster-prone areas, processing of secondary data, and analysis using remote sensing. The results of this study are that the rocks in the West Bandung area are divided into groups of volcanic rocks, sedimentary rocks, and alluvial deposits. The volcanic rock group got a score of 3 because it was considered more prone to erosions than the sedimentary and alluvial rock groups which were scored 2 and 1. with a weighted level of disaster vulnerability. The zone of high disaster susceptibility is considered to have the highest probability of a disaster occurring. Therefore, in the final result, the overlap between the distribution of the potential for minerals and the zone of high disaster susceptibility results in a potential area for minerals that are relatively safe from disasters, both soil movement, and flooding. Potential mining resources in West Bandung Regency are Andesite basalt 1,860,412 ha (1.43%), Limestone 667.05 ha (0.50%), Sirtu 40,949.76 ha (31.35%%).